Sobre verbos eponímicos - Martínez Linares, Antonia (Acta Hispanica, 2011)
This paper analyses the basic meaning underlying eponymic verbs which are derived from a currentpolitician surname by the sujfixation of -igar, and the way of capturing their diverse lectures. I arguethat these verbs share with other denominál verbs an underspecified causative meaning and that theirinterpretation, like the lectures of denominál verbs in general, is modulated by sublexical or encyclopedicinformation of the predicate arguments and of the base nouns.